2016
DOI: 10.1371/journal.pone.0160485
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Antibody Monotherapy for Malignant Melanoma: A Systematic Review and Meta-Analysis

Abstract: Antibodies targeting programmed death 1 (PD-1) help prevent tumor cells from escaping immune-mediated destruction. We conducted this systematic review and meta-analysis to gain insight into the efficacy of PD-1 antibodies for the treatment of melanoma. Five trials involving 2,828 adult patients were included in this meta-analysis. In patients with previously untreated or refractory melanoma, treatment with PD-1 antibodies significantly improved the six-month progression-free survival (PFS) (HR 0.55, 95% CI 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…Previous meta-analyses have evaluated the efficacy of ICIs. [30][31][32][33][34][35][36][37][38] Some concluded that combination immunotherapy could result in better antitumor efficacy, but were based on only one or two studies. 31,38 One network meta-analysis compared ICIs with targeted therapies for metastatic melanoma, suggesting that a combination of BRAF and MEK inhibitors was superior to anti-CTLA-4 agents and anti-PD-1 agents.…”
Section: Agreement/disagreement With Previous Meta-analysesmentioning
confidence: 99%
“…Previous meta-analyses have evaluated the efficacy of ICIs. [30][31][32][33][34][35][36][37][38] Some concluded that combination immunotherapy could result in better antitumor efficacy, but were based on only one or two studies. 31,38 One network meta-analysis compared ICIs with targeted therapies for metastatic melanoma, suggesting that a combination of BRAF and MEK inhibitors was superior to anti-CTLA-4 agents and anti-PD-1 agents.…”
Section: Agreement/disagreement With Previous Meta-analysesmentioning
confidence: 99%
“…The development and therapeutic potential of immune checkpoint inhibitors (ICPIs) has fundamentally changed cancer treatment paradigms across multiple tumor types. However, only a subset of patients treated with ICPIs experience durable clinical responses . Ongoing optimization of ICPI treatment requires additional predictive biomarkers that further establish which patients are most likely to benefit from such therapies.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the normal functions of T lymphocytes were suppressed in numerous types of solid tumors, resulting in reduced antitumor immunity and evasion of host immune surveillance (16,17). As an inflammatory factor, PD-1 exhibited marked immunosuppressive effects in a number of different types of tumors (18,19). In order to determine the change in the number of PD-1 + T cells during the progression of lung cancer, the levels of PD-1 expression in infiltrating CD4…”
Section: Expression Of Pd-1 In Infiltrating Cd8mentioning
confidence: 99%